Portal Venous Interventions after Liver Transplant - Mahon, Scott; Molvar, Christopher (Digestive Disease Interventions, 2019)
Liver transplant (LT) recipients are a challenging patient population when presenting with graft dysfunction or sequelae of portal hypertension. When no medical causes for graft dysfunction are found, a hemodynamically significant vascular lesion is suspected. Although rare, a variety of diseases may arise involving the portal system, which inhibit flow and graft function. Herein, we present a review of portal venous interventions performed in the LT setting, with focus on imaging diagnosis, endovascular treatment techniques, and outcomes. Entities addressed include portal venous stenosis, portal venous thrombosis, and recurrent fibrosis/cirrhosis with sequelae of portal hypertension.
Keywords: liver transplant; portal vein; endovascular interventions